The Impact of Market Maker Competition on Market Quality: Evidence from an Options Exchange - Angelo Aspris; Alex Frino; Andrew Lepone (Australasian Accounting, Business and Finance Journal, 2013)
This paper examines the dynamic relationship between competition, liquidity provision, and market structure. By examining the entry and exit of market makers in the Australian Options market, this study empirically analyses the issue of market maker competition. Results indicate that market maker entry depends on a broad range of profit, risk and market concentration characteristics, but free market maker movement does not explicitly result in a competitive market structure. This study also finds that the degree of market concentration additionally affects the marginal impact of market maker entry (exit), but the effect is significantly more pronounced for the most liquid classes of options. The implication of this finding is pertinent to market regulators since market maker competition may not necessarily contribute to enhancing market quality for less liquid securities.
Keywords: Options; Market Makers; Liquidity; Market Quality